Inovasi Pelayanan Publik Berbasis SP4N Lapor Pasca Pandemi Covid - 19 Di Diskominfo Kota Banjar - Alin Kristina (Pusat Riset dan Inovasi Nasional, 2023)
Digital-based public services are an effort to overcome the limitations of public services directly in order to prevent the spread of Covid-19.So that digital innovation is needed in public services so that effective and efficient. Public services are all forms of services, both in the form of public goods and public services. However, the implementation of public services does not always go as expected, there are certain things that make the public services provided tend to be less good. Based on this, this research study aims to determine the quality of public services and the factors that support and hinder public services. The formulation of the problems raised in this study are as follows: 1. How is SP4N LAPOR-Based Public Service Innovation After the Covid-19 Pandemic at Diskominfo, Banjar City? 2. What are the supporting and inhibiting factors for SP4N LAPOR-Based Public Service Innovation in the Post-Covid-19 Pandemic at Diskominfo, Banjar City? This study uses qualitative methods to describe public services based on SP4N LAPOR (National Public Service Complaint Management System for People's Online Aspirations and Complaint Services). Informants were selected by purposive sampling consisting of the Diskominfo admin team, liaison officials and the SP4N LAPOR user community. Research data was collected using observation, interviews and documentation. The research results show 1). physical evidence (tangible) 2). reliability (reliability) 3). responsiveness (responsiveness) 4). guarantee (assurance) 5). and empathy. everything has been going well except for the physical evidence indicators which still need to be improved, especially in terms of communication media. As for those that support services, namely internal communication and human resources and system support, however, there are also those that hinder them, namely human resources and applications that sometimes have errors.